PROTECTION OF THE RIGHTS OF SUSPECTS DURING THE DETENTION PROCESS BASED ON THE CRIMINAL PROCEDURE CODE - Nafilah Amalia; Ardiyanti Aris; Lilis Suryani; Sunardi Purwanda; Muhammad Darwis (PT. Radja Intercontinental Publishing, 2026)
As a nation governed by the rule of law, Indonesia has an obligation to guarantee the protection of human rights for every citizen, including those facing criminal proceedings, particularly during the detention phase, which constitutes the most intrusive form of coercion against individual liberty. This study aims to examine the regulations governing the rights of suspects during the detention process as specified in the Criminal Procedure Code and to analyze the forms of legal protection provided for these rights. This study employs a normative legal research method using both a statutory and a conceptual approach, with primary legal sources consisting of Law No. 20 of 2025 on the Criminal Procedure Code, the 1945 Constitution of the Republic of Indonesia, Law no. 48 of 2009 on Judicial Power, and the International Covenant on Civil and Political Rights. The research findings indicate that the New Criminal Procedure Code comprehensively regulates the rights of suspects in Article 142, covering the right to legal counsel from the arrest and detention stages, the right to contact family members, the right to health care, and the right to file a pretrial motion—the scope of which (both in terms of subject matter and eligible parties) has been significantly expanded—accompanied by stricter detention requirements through three cumulative conditions: objective, subjective, and formal criteria, including the mandatory appointment of a Preliminary Examination Judge. As for the forms of legal protection for the rights of suspects based on Philipus M. Hadjon's theory, they encompass two dimensions: preventive protection, realized through the mandatory appointment of a Preliminary Examination Judge, the guarantee of legal aid from the outset of the investigation, an absolute prohibition on torture as a non-derogable right, and a multi-layered oversight system through internal and external channels, as well as repressive protection realized through the strengthening of pretrial proceedings—whose scope of application has been significantly expanded—and mechanisms for compensation and rehabilitation, which are now regulated in a separate chapter. Collectively, these reflect a paradigm shift in Indonesia's criminal justice system toward one that genuinely upholds the protection of suspects' human rights.